Seasonal variation in animal diversity in agricultural fields (Zoological Records and Reviews, 2022)
Agricultural fields represent the dominant land use in much of the world's terrestrial surface, yet the seasonal dynamics of animal diversity within these landscapes remain poorly understood compared to natural ecosystems. Understanding how animal communities change across crop phenological stages and between cultivation seasons is essential for designing agri-environment interventions that benefit biodiversity across the full agricultural calendar. This study documents seasonal variation in animal diversity across five animal groups -- ground beetles (Carabidae), spiders (Araneae), birds, small mammals, and herpetofauna -- in paddy rice, dryland pulse, and mixed horticulture agricultural fields in the Krishna-Godavari delta region of Andhra Pradesh, India, sampled monthly over two complete agricultural cycles (2019-2021). A total of 412 animal species were documented across all groups and field types, with pronouncedseasonal turnover driven by crop phenology, monsoon flood pulses, and post-harvest habitat restructuring. Paddy fieldsduring the flood irrigation phase support the highest total diversity (mean 84.4 species per site per season) owing to thetemporary creation of wetland habitat. Ground beetles show the most pronounced seasonal amplitude, with speciesrichness varying 4.8-fold between peak (post-monsoon sowing) and minimum (peak flood) periods. Birds show thehighest seasonality driven by migratory influx, with 38.4% of recorded bird species being seasonal visitors. Pesticideapplication events are associated with significant short-term (2-4 week) reductions of 32-48% in ground beetle and spiderabundance. Conservation and management recommendations for maintaining biodiversity across the agriculturalseasonal cycle are presented.
Keywords: temporal turnover; farmland biodiversity; pesticide impact; crop phenology; Krishna-Godavari delta; paddy rice; Araneae; Carabidae; agricultural fields; seasonal diversity